Discovery of polymethoxyflavones from black ginger (Kaempferia parviflora) as potential β-secretase (BACE1) inhibitors. (January 2016) - Youn, Kumju; Lee, Jinhyuk; Ho, Chi-Tang; Jun, Mira
Highlights: 5, 7-DMF, 5, 7, 4′-TMF, and 3, 5, 7, 3′, 4′-PMF were discovered as novel BACE1 specific inhibitors. DMF, TMF, and PMF suppressed BACE1 activity with IC50 value of 4.95 × 10 −5  M, 3.69 × 10 −5  M, and 5.98 × 10 −5  M, respectively. DMF, TMF, and PMF were non-competitive inhibitors with a substrate interacted with allosteric sites of BACE1. Abstract: Inhibition of β-site amyloid precursor protein cleaving enzyme 1 (BACE1) has emerged as a prime target in Alzheimer's disease research because BACE1 is the rate-limiting enzyme involved in the abnormal production of β-amyloid peptides. In the course of exploring natural BACE1 inhibitors, the present study focused on the major polymethoxyflavones from Kaempferia parviflora : 5, 7-dimethoxyflavone (DMF), 5, 7, 4′-trimethoxyflavone (TMF), and 3, 5, 7, 3′, 4′-pentamethoxyflavone (PMF). All polymethoxyflavones exhibited strong BACE1 inhibitory potency, with no significant suppression of α-secretase or other serine protease activities, indicating that they were relatively specific and selective BACE1 inhibitors. Dixon and Lineweaver–Burk plots indicated that they produced non-competitive inhibition of substrate cleavage. An in silico docking study of human BACE1 with polymethoxyflavones demonstrated the binding energy and the interacting residues. Our findings indicated that Kaempferia parviflora could provide a novel therapy for the prevention of Alzheimer's disease and provide a scaffold for exploration of more potent natural BACE1 inhibitors.